COMPARISON OF AUTOREGRESSIVE (AR) STRATEGY WITH THAT OF REGRESSION APPROACH FOR DETERMINING OZONE LAYER DEPLETION AS A PHYSICAL PROCESS - K. Yousaf Zai, M. A.; Ansari, R. K.; Qaumar, J.; Iqbal, J.; Hussain, M. A. (The Nucleus, 2010)
This communication presents the development of a comprehensive characterization of ozone layer depletion (OLD) phenomenon as a physical process in the form of mathematical models that comprise the usual regression, multiple or polynomial regression and stochastic strategy. The relevance of these models has been illuminated using predicted values of different parameters under a changing environment. The information obtained from such analysis can be employed to alter the possible factors and variables to achieve optimum performance. This kind of analysis initiates a study towards formulating the phenomenon of OLD as a physical process with special reference to the stratospheric region of Pakistan. The data presented here establishes that the Auto regressive (AR) nature of modeling OLD as a physical process is an appropriate scenario rather than using usual regression. The data reported in literature suggest quantitatively the OLD is occurring in our region. For this purpose we have modeled this phenomenon using the data recorded at the Geophysical Centre Quetta during the period 1960-1999. The predictions made by this analysis are useful for public, private and other relevant organizations.